Lipopolysaccharide priming of human neutrophils for an enhanced respiratory burst. Role of intracellular free calcium. - Forehand, J R; Pabst, M J; Phillips, W A; Johnston, R B, Jr (The Journal of Clinical Investigation, 1989)
Lipopolysaccharide (LPS) pretreatment "primes" neutrophils to release increased amounts of superoxide anion (O2-) when stimulated. We investigated the molecular basis of this enhanced activity. Comparison of kinetic parameters of the respiratory burst NADPH oxidase in unstimulated LPS-primed and control neutrophils disclosed a similar Km for NADPH and no difference was seen in the content of cytochrome b. Pertussis toxin, which inhibits some G proteins, did not prevent priming. Change in membrane potential (delta psi) was five-fold greater in LPS-primed cells and paralleled the increased O2- release. Cytofluorographic analysis indicated that the increased change in delta psi was due to the creation of a new population of active cells. Changes in the concentration of intracellular free Ca2+ ([Ca2+]i) are believed to antecede changes in delta psi. There was a consistent increment (67 +/- 8%, n = 12) in resting [Ca2+]i in cells preincubated with LPS compared with control. When stimulated, the peak [Ca2+]i was significantly higher in LPS-primed cells. Ca2+-dependent protein kinase C activity was unaltered in resting and FMLP-stimulated neutrophils preexposed to LPS. Addition to cells of the intracellular Ca2+ chelator MAPTAM before preincubation with LPS blocked the changes in [Ca2+]i and the enhanced respiratory burst that characterize LPS priming. The increased resting [Ca2+]i in LPS-primed cells may enhance stimulus-induced cellular activity by modifying a Ca2+-dependent step in signal transduction.